Does Fintech Affect Consumer Retention in Islamic Banks? Empirical Evidence from OIC Countries - Khan, Safeer Ullah; Sumarliah, Eli (UNISSULA, 2024)
FinTech is a trendy topic that has increased rapidly in Organization of Islamic Cooperation (OIC) countries, where Muslim consumers desire to use banking services in a Sharia conforming way. Thus, the research seeks to examine the effect of FinTech applied by Islamic banks of OIC countries on consumer retention. The Islamic banking system in OIC nations has mainly been in the foreground in carrying FinTech to its operations at the initial phase. Although consumers typically do not select Islamic banks for technologies, the study tries to investigate the effect of FinTech in maintaining consumers. Data collection uses the strata sampling method; online questionnaires are spread and collected from 317 customers of chosen banks in OIC countries. SPSS 25.0 analyzes statistical data via numerous examinations such as regression analysis, factor analysis, sample adequacy, and reliability analysis. The results show that compliance, consulting services, and payments of FinTech affect consumer retention. However, financing services considered vital in conventional banks do not significantly influence consumer retention. The research tries to help Islamic banks satisfy their consumers by using FinTech applications and helping FinTech firms enhance their finance amenities.